Second Annual Travelling Meeting of the XYdigitale Project and the XY Journal (diségno, 2021)
For almost 20 years, several events have radically, and in our opinion permanently, changed the scientific publishing. For example, in 1997 was born Web of Science [1]; in 1999 starts Open Access Initiative [2]; in 2002 was signed the Budapest Open Access Initiative [3], followed in 2003 by Berlin Declaration on Open Access to Knowledge in the Sciences and Humanities [4] and in 2004 by the Dichiarazione di Messina [5]; also in 2004, Elsevier made Scopus available online [6] (read more).